Development and Validation of an Instrument to Measure Quality and Benefits for Work-based Learning Implementation - Mohd Samshul, Siti Nurafiqah; Mohamad, Mimi Mohaffyza; Miskon, Muhammad Fahmi; Khalid Khan, Nur Liyana; Sahrin, Suhaimi (Online Journal for TVET Practitioners, 2026)
This study aimed to develop and validate a measurement instrument to assess students’ experiences of the quality and benefits of Work-Based Learning (WBL) implementation within Malaysia’s Technical and Vocational Education and Training (TVET) sector. Given the need for a psychometrically robust tool capable of producing interval-level measurement and ensuring item-level diagnostic precision, the Rasch measurement model was employed to evaluate construct validity, reliability, unidimensionality, and item functioning. A total of 68 students enrolled in Ministry of Higher Education WBL programs participated in the study by responding to an online questionnaire. Data was analyzed focusing on person and item reliability indices, separation statistics, item polarity, fit statistics, standardized residual correlations, and the alignment between item difficulty and respondent ability. The analysis demonstrated excellent internal consistency and satisfactory item polarity across all items. Fourteen items initially indicated misfit; following diagnostic evaluation, one item was removed and one revised, resulting in a final 50-item instrument. The validated instrument satisfies Rasch model assumptions of unidimensionality and local independence, confirming its suitability for measuring students’ perceptions of WBL quality and benefit dimensions. This instrument provides educators, researchers, and policymakers with a reliable evaluative tool to strengthen WBL implementation and industry engagement in the Malaysian TVET context.